2003
DOI: 10.2170/jjphysiol.53.181
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor, Capillarization, and Function of the Rat Plantaris Muscle at the Onset of Hypertrophy.

Abstract: Skeletal muscle has a great ability to respond to altered functional demands. This response includes, among other adaptations, changes in muscle size, fiber-type composition, and capillary supply, resulting in altered contractile properties and fatigue resistance [1]. The response to the increased functional demand imposed on a muscle by the elimination of agonist muscles involves compensatory hypertrophy. This hypertrophy is accompanied by an increase in the number of type I fibers and capillary proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
3
12
0
Order By: Relevance
“…Another factor that may induce angiogenesis during growth is the slow but gradual elongation of the muscle during normal growth, causing a chronic mechanical stretch on the muscle and the vessels therein ( 34 ), via induction of HIF and the endothelial mitogen vascular endothelial growth factor (VEGF). Similar to what we report here for normal growth, angiogenesis during compensatory hypertrophy resulted in increased C:F but reduced CD ( 10 ), and was preceded by elevated levels of VEGF ( 6 ).…”
Section: Discussionsupporting
confidence: 84%
“…Another factor that may induce angiogenesis during growth is the slow but gradual elongation of the muscle during normal growth, causing a chronic mechanical stretch on the muscle and the vessels therein ( 34 ), via induction of HIF and the endothelial mitogen vascular endothelial growth factor (VEGF). Similar to what we report here for normal growth, angiogenesis during compensatory hypertrophy resulted in increased C:F but reduced CD ( 10 ), and was preceded by elevated levels of VEGF ( 6 ).…”
Section: Discussionsupporting
confidence: 84%
“…It is interesting to note, however, that a number of recent studies have observed regional differences in plantaris muscle capillarity (i.e. deep oxidative and superficial glycolytic regions; Degens et al 2003; Zoll et al 2003; Wust et al 2009 a , b ). These studies revealed that the deep oxidative regions have higher capillary density than the superficial glycolytic regions.…”
Section: Discussionmentioning
confidence: 99%
“…The mean soleus fiber CSA was not changed by 3 days of overload or nandrolone decanoate pretreatment. However, mean CSA is not an accurate description of the remodeling events occurring in overloaded skeletal muscle (20). An increased incidence of very small-diameter myofibers in skeletal muscle is an established indicator of regeneration from injury (15,30,55,56).…”
Section: Discussionmentioning
confidence: 99%